Modul Pembelajaran Sains dengan Pendekatan Inkuri untuk Mengembangkan Keterampilan Proses Sains Dasar Siswa Tunarungu - Mulyeni, Trisna; Lianty, Leliana (Jurusan Pendidikan Luar Biasa Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2021)
The aim of the study was to produce teaching material as a learning module for teachers, in order to develop basic science process skill for hearing impairments students. Science process skills are an important aspect in learning science. Teachers need teaching materials as a source of relevant knowledge and skills in order to implement science learning especially in developing science process skills. For this reason, a specific module was developed for teachers to teach science process skills through an inquiry approach for hearing impairments students. Specific aim of the study was to examine the feasibility of the module as a product being developed. This study used the method of Research & Development. The subjects of the study were classroom teachers and fifth grade of hearing impairments students. An instrument for product validation testing was developed and given to relevant experts. Data analysis was carried out qualitatively and quantitatively. The results of the expert validation test showed that the module has a feasibility level of 87%, which categorized as a very feasible product.